Peran Penilaian Kerja dan Kompensasi dalam Meningkatkan Kinerja Tutor di PKBM Prestasi Gemilang - Agus Hidayat, Handi; Zuniarti, Astrini; Romdhoni, Ahmad; Helmin; Mulyadi, Edi (Plexi Digital Indonesia, 2025)
This study examines the roles of performance appraisal and compensation in enhancing tutor performance within a nonformal education setting at PKBM Prestasi Gemilang. Adopting a quantitative descriptive approach, data were collected via a Likert-scale questionnaire from 53 active tutors. Instrument quality was established through validity and reliability testing, and relationships among variables were analyzed using multiple regression. The findings indicate that both performance appraisal and compensation are positive predictors of tutor performance, with appraisal emerging as the more salient driver when it is objective, transparent, and accompanied by targeted feedback. Compensation both financial and nonfinancial strengthens motivation, loyalty, and retention, reinforcing the impact of appraisal on day-to-day teaching practice. Theoretically, the results affirm the relevance of performance management as a continuous cycle and align with Herzberg’s two-factor theory in the context of community learning centers. Practically, the study recommends formalizing indicator-based appraisal systems, linking appraisal outcomes to professional development, and structuring equitable, transparent compensation packages. Limitations include the cross-sectional design, single-site context, and reliance on self-report measures. Future studies should broaden the institutional scope, employ longitudinal designs, incorporate mediators or moderators (e.g., motivation, work environment, organizational support), and integrate learner outcomes and classroom observation into the appraisal cycle